Recent advances in catalysts for the Henry reaction - Bao, Xuefei; Li, Xu; Jiang, Chunfeng; Xiao, Wei; Chen, Guoliang (Australian journal of chemistry, 2022)
The Henry reaction, the coupling of a nitro alkane and a carbonyl group, is an important C–C bond-forming reaction giving nitro alkanols, which are useful, versatile intermediates in synthetic organic chemistry and for the pharmaceutical industry. Among the catalysts employed in the Henry reaction, transition metal complex catalysts play an important role. Transition metal complexes, including small molecules and nanoparticles, catalyze the asymmetric Henry reaction efficiently and in most of the cases give chiral nitro alkanol products in good yield and enantiomeric excess. This review summarizes transition metal complex catalysts, metal-free organic catalysts and nanoparticle catalysts for the Henry reaction.